Participant Chinese teacher and student perceptions of an international teaching practicum with Australian pre-service teachers. Issue 6 (1st November 2020) - Jin, Aijing; Foley, Annette; Cooley, Dean
ABSTRACT: Insights into local Chinese teacher and student views of an international teaching practicum with Australian pre-service teachers are the focus of this paper. A qualitative content analysis was undertaken on teacher and student accounts captured through individual interviews with four teachers and questionnaire survey with 186 students. The paper uncovers how teachers and students perceived what they experienced in the practice of intercultural communication on teaching and learning. Emphasised in the analysis is the importance of situating discussions within the Chinese social cultural context, acknowledging the influence of traditional Chinese cultural values and educational conceptions on their teaching and learning practice. The findings reveal meaningful insights into intercultural comprehension involving teaching strategies, learning content and assessment and classroom management. The study's findings highlighted that this international teaching practicum was a beneficial and valuable experience for participant Chinese students and teachers. The study also highlighted a potential gap in the preparation of Australian pre-service teachers and the Chinese students and Chinese teachers, regarding culturally specific and culturally aware competencies.